The inventive schoolmaster : Simón Rodríguez - Kohan, Walter Omar (SensePublishers, 2015)
ĹℓA constant belief seems to give life to Kohanℓ́ℓs theoretical work and philosophical practice. A supposition that one could never prove, or disprove, motivates Kohanℓ́ℓs ceaseless erring and essaying, his efforts to invent school. We read it in-between the lines of nearly all of his published work, and those who have had the chance to take part in his manner of philosophical ask♯ℓsis feel it in his practice. It is a belief that he shares with Rodr©Ưguez: All children, adolescents, and adults, from all walks of life, from any corner of the globe, no matter their economic status, occupation, gender, race, or ethnicity, can philosophize. But perhaps more profoundly, and it is here where I think Kohanℓ́ℓs written work and practice mirror the pedagogy and text of Rodr©Ưguez, philosophizing, living philosophically, with anyone, for anyone, we can invent school. The Inventive Schoolmaster: Sim©đn Rodr©Ưguez is indeed about the inventive Sim©đn Rodr©Ưguez. More importantly, however, it is an essay which shows us how a life of philosophical essaying and errantry can invent school. And in this regard it is also an introduction to the singular form of Walter Kohanℓ́ℓs philosophy of education.ℓ́ℓ ℓ́ℓ Jason Thomas Wozniak.